Ensino de leitura na EJA: análise das narrativas de formação de professores de 4º ciclo - Linhares, Allan de Andrade (2017)
The object of study of this research are the formative processes of the reading instructor-learner of EJA (Brazilian youth and adult education program) revealed from their oral narratives of life and formation, motivated by the following guiding questions: How does the reading teaching happens in the perspective of the discourses produced through the reports of life and the formation of EJA instructor-learners of municipal public schools in Parnaíba-PI? What conceptions and practices of reading, language and teaching do emerge from the discourses present in these narratives? What are the conceptions of reading and the practices adopted by teachers in the proposed guidelines for the study of texts? In order to answer the guiding questions, the following objectives were delineated: Main Objective: To investigate the conceptions and practices of reading, discursively constructed, in the reports of life and formation of the instructor-learner to develop the teaching of reading. Specific: 1) To analyze and characterize, from the observations of classes, the conceptions and strategies of reading adopted by the instructor-learner in the directions for the study of texts; 2) Reflect about discourses produced in the narratives of life and formation, verifying what they interpret about the conceptions and strategies of reading adopted in the daily life of reading orientations; 3) To verify the relationship between the discourses, theoretically constructed by the instructor-learner about their stories of life and reading, and the discourses constructed in the classroom practice; 4) To identify how the story of life and formation influenced the history of reading and teaching of reading performed by the instructor-learners researched; 5) Propose, from the assumptions of Linguistic Education, reflections on more productive referrals to work with some textual genres during pedagogical workshops. A narrative research was developed, with qualitative approach, dialoguing with authors such as Ferrarotti (1988), Clandinin and Connelly (2011), Suárez (2008), Josso (2004, 2010), among others. These authors suggest that the narrative centered on the formative pathways makes it possible to enhance the formative character of this process. For the accomplishment of the research, three instructor-learners of schools of 4º cycle of EJA from Parnaíba-PI collaborated. In order to achieve the objectives sought in the research we made classes observations of the participants during three months. Subsequently, we proceeded to the production of oral narratives in order to provide an unveiling of the occult of their discourse, how was constituted their history of life, reading and formation. The data produced from these first two stages of the research were analyzed in the light of the theoretical reference of the formative experiences and the narratives, besides the framework of the Linguistic Education. The narratives revealed that there is a close relation between the discourses produced for the teaching of reading and the experiences of family contexts, schooling and formation. The third stage of the research consisted of three pedagogical workshops (CANDAU, 1995), active methodology modality (PALMA, 2016; BERBEL, 2011), carried out during the interactive meetings. At the end of the workshops, which involved exchanges of experiences and theoretical studies, which were previously available, it was possible to realize, in the speeches produced by the instructor-learners, the theoretical-methodological collaboration brought by the pedagogical resource